Geguritan Runtuh Watugunung (Analisis Struktur Dan Psikologi Tokoh) - Ardika, Kadek; Asli, Luh (Jayapangus Press, 2024)
Literature is a work that is bound by beautiful characters and language. On the island of the gods, Bali, there are many literary works that are still alive and developing in society, these literary cases are divided into two, namely Bali Purwa literature and New Balinese Literature. One type of literary work that is included in Bali Purwa literature namely in the form of poem. The geguritan that will be discussed in this research are: Poem Ruthu Watugunung. The aim of this research is to analyze the structure and psychology of the characters in the story Poem Rutuh Watugunun. This research uses a qualitative descriptive research type. The data analysis technique in this research was carried out descriptively based on research results obtained through observation, interviews and documentation with data analysis carried out through data reduction and data presentation. The results of this research show an intrinsic structure such as: incidents, namely there are ten incidents, using a forward plot, there are nine characters and characterizations, there are three settings, namely time setting, place setting and atmospheric setting. poem This is about forbidden love. And there is a message contained, namely about love and heroism. Extrinsic structures such as: literary psychology, namely the psychology of the author, the psychology of the reader and the psychology of the characters A poem about the collapse of Watugunung. In this poem there are various types of puns in it that tell the story from the beginning to the end of the story A poem about the collapse of Watugunung, and in this poem is able to recognize the state or psychology of a character that can take positive things and can also be used as a lesson in life.